36×2-84x+49=0

Rewrite 36×2 as (6x)2.

(6x)2-84x+49=0

Rewrite 49 as 72.

(6x)2-84x+72=0

Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.

2ab=2⋅(6x)⋅-7

Simplify.

2ab=-84x

Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=6x and b=-7.

(6x-7)2=0

(6x-7)2=0

Set the 6x-7 equal to 0.

6x-7=0

Add 7 to both sides of the equation.

6x=7

Divide each term by 6 and simplify.

Divide each term in 6x=7 by 6.

6×6=76

Cancel the common factor of 6.

Cancel the common factor.

6×6=76

Divide x by 1.

x=76

x=76

x=76

x=76

Solve Using the Square Root Property 36x^2-84x+49=0